FACTORIAL ANALYSIS STRUCTURE OF "PATA NEGRA" TEST - Yárnoz Yaben, Sagrario (Anales de Psicología / Annals of Psychology)
The aim of this work is to analize the factor structure underlying Corman's test Patte Noire. We tested 98 children of the countryside of Guipúzcoa, following the author's critheria.Children's answers were clasified in 20 cathegories wich were found in the stories told by them. This answer cathegories had to pass the blind judge test. Acord porcentages among four judges varied from 0.62 to 1.00.Factor analysis was performed on this cathegories using the SPSS/PC+ program, and the following eight factor came out: frustrating mother, deffending mother/father form danger, orality, authority, agresivity of the parental fidgures, substitutive mother/father, ludic relation with mother/father, and agresivity directed against the father. Those factors proved to be related to the preferences of children toward mother or father in mildly stress situation, evaluated through cuestionary, and the attitudes and decision capacity of mothers.